Hubungan Fleksibelitas Pergelangan Tangan Dengan Ketepatan Pukulan Fourhand Tenis Meja Mahasiswa PKO FIK UNIMED - Kurniawan, Rizkei; Haryanto, *Jeki; Purnomo, Eko (Ilmu Olahraga, 2020)
This study aims to determine whether wrist flexibility is related to the accuracy of the fourhand table tennis in PKO students of the UNIMED sports science faculty. The accuracy of the strokes is influenced by several factors such as hand eye coordination, wrist flexibility, training motivation and so on. Based on the author's observation, not all students who take table tennis elective courses master basic tennis techniques such as forehand. When the ball is hit with a forehand stroke, the ball does not aim and looks like it is out of control. A player who can maximize wrist flexibility, will be able to control the ball well and can return the ball in difficult positions. The ability of the forehand is also affected by the flexibility of the wrist. Players who have good wrist flexibility will get forehand hits that are well targeted. In the hypothesis it is said that there is a significant relationship between wrist flexibility (X) and the accuracy of table tennis forehand (Y) in PKO Unimed students. Based on the results of hypothesis testing, the relationship between the two variables is proven where there is a significant relationship. The result of the correlation coefficient (ry.x) is 0.4788 with a determination coefficient of 22.92%. This means that wrist flexibility has a strong positive relationship. Flexibility of the wrist can affect the accuracy of table tennis forehand strokes by 22.92%, while 77.08% is determined by other variables. By having good wrist flexibility, the accuracy of the table tennis forehand will be good too.